THE TRANSITION OF ALBANIA FROM REPUBLIC TO MONARCHY - Lavdosh Ahmetaj (European Scientific Journal, ESJ, 2014)
The transition of Albania from Republic to Monarchy has been one of the most important point in the history of Albania and its people. That moment influenced in many historic events in the life of Albanians. The National Assembly on January of 1925 proclaimed Albania a republic and elected Zog President for a seven years period. On Saturday, the 1st September this amendments were approved by the Assembly, and Ahmet Zog proclaimed “Zog I, King of the Albanians”. The new king to be Ahmet Zogu was the person that decided for the new system in Albania. The aim of this article is to make a chronological description of that important moment for Albania and bring some new facts from sources of that time.